Spin-density correlator and its Fourier transform in the dynamic spin-fluctuation theory - Paradezhenko, G.V.; Melnikov, N.B.; Reser, B.I. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2016)
A formula relating the magnetic contribution to a polarized neutron scattering cross-section with the Fourier transform of the spin-density correlator is derived. A method of calculating the spin-density correlator and its Fourier transform in the dynamic spin-fluctuation theory is described. Calculation formulas and Fortran program modules are presented. By the example of iron, it is shown that the numerical results obtained for the Fourier transform of the spin-density correlator are in good agreement with experimental data.